Publish/subscribe systems : design and principles - Tarkoma, Sasu. (Chichester, West Sussex, UK : John Wiley & Sons, 2012)
This book offers an unified treatment of the problems solved by publish/subscribe, how to design and implement the solutionsIn this book, the author provides an insight into the publish/subscribe technology including the design, implementation, and evaluation of new systems based on the technology. & nbsp; The book also addresses the basic design patterns and solutions, and discusses their application in practical application scenarios. Furthermore, the author examines current standards and industry best practices as well as recent research proposals in the area. Finally, necessary content match.
Networking and messaging -- Overlay networks and distributed hash tables -- Principles and patterns -- Standards and products -- Web technology -- Distributed publish/subscribe -- Matching content against constraints -- Research solutions -- IR-style document dissemination in DHTs -- Advanced topics -- Applications -- Clean-slate datacentric pub/sub networking.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Push technology (Computer networks); Electrical engineering; Computer science; Engineering; COMPUTERS -- Web -- Podcasting & Webcasting; Push technology (Computer networks); Electronic books; Electronic books